2019
DOI: 10.3390/s19092144
|View full text |Cite
|
Sign up to set email alerts
|

Routing Protocols for Low Power and Lossy Networks in Internet of Things Applications

Abstract: The emergence of the Internet of Things (IoT) and its applications has taken the attention of several researchers. In an effort to provide interoperability and IPv6 support for the IoT devices, the Internet Engineering Task Force (IETF) proposed the 6LoWPAN stack. However, the particularities and hardware limitations of networks associated with IoT devices lead to several challenges, mainly for routing protocols. On its stack proposal, IETF standardizes the RPL (IPv6 Routing Protocol for Low-Power and Lossy Ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(53 citation statements)
references
References 94 publications
0
42
0
1
Order By: Relevance
“…One of the major drawbacks of the current IoT scenario is the presence of different technologies and solutions proposed by independent vendors to enable networking among objects. This poses the basis to a subsequent set of issues ranging from concept matching to technical compatibility, if heterogeneous smart-object-network solutions should be involved in the creation of a unique interoperable IoT [42,43]. In this research context, different works partially addressing and solving these problems have been proposed.…”
Section: Related Literaturementioning
confidence: 99%
“…One of the major drawbacks of the current IoT scenario is the presence of different technologies and solutions proposed by independent vendors to enable networking among objects. This poses the basis to a subsequent set of issues ranging from concept matching to technical compatibility, if heterogeneous smart-object-network solutions should be involved in the creation of a unique interoperable IoT [42,43]. In this research context, different works partially addressing and solving these problems have been proposed.…”
Section: Related Literaturementioning
confidence: 99%
“…After much effort from various research communities a standardized version of RPL protocol was released to have a common routing protocol for IP based WSNs. RPL aims at constructing a multi hop mesh topology utilizing a set of lossy links between the nodes [13]. RPL is a gradient based routing algorithm and many performance studies revealed that it has reliability issues.…”
Section: Related Workmentioning
confidence: 99%
“…The smart devices have limited memory, processing power, and reduced battery life which makes IoT scenarios a Low-Power and Lossy Networks (LLNs) [18]. Thus, the Routing over Low-Power and Lossy Networks Working Group (RoLL WG) addresses IoT LLN scenarios which provide solutions that enable communication between smart devices.…”
Section: Introductionmentioning
confidence: 99%